MesoTIPS: Combined Approach for the Treatment of Portal Hypertension Secondary to Portal Vein Thrombosis – A Brief Report - Abbas Chamsuddin; Lama Nazzal; Thomas Heffron; Osama Gaber; Raja Achou; Louis G. Martin (The Arab Journal of Interventional Radiology)
Introduction: We describe a technique we call “Meso-transjugular intrahepatic portosystemic shunt (MTIPS)” for relief of portal hypertension secondary to portal vein thrombosis (PVT) using combined surgical and endovascular technique. Materials and Methods: Nine adult patients with PVT underwent transjugular intrahepatic portosystemic shunt through a combined transjugular and mesenteric approach (MTIPS), in which a peripheral mesenteric vein was exposed through a minilaparotomy approach. The right hepatic vein was accessed through a transjugular approach. Mechanical thrombectomy, thrombolysis, and angioplasty were performed when feasible to clear PVT. Results: All patients had technically successful procedures. Patients were followed up for a mean time of 13.3 months (range: 8 days to 3 years). All patients are still alive and asymptomatic. Conclusion: We conclude that MTIPS is effective for the relief of portal hypertension secondary to PVT.